The Matrix in theory - Díaz-Diocaretz, Myriam; Herbrechter, Stefan (Amsterdam ; New York : Rodopi, 2006)
The Matrix trilogy continues to split opinions widely, polarising the downright dismissive and the wildly enthusiastic. Nevertheless, it has been fully embraced as a rich source of theoretical and cultural references. The contributions in this volume probe the effects the Matrix trilogy continues to provoke and evaluate how or to what extent they coincide with certain developments within critical and cultural theory. Is the enthusiastic philosophising and theorising spurred by the Matrix a sign of the desperate state theory is in, in the sense of "see how low theory (or 'post-theory') has sunk.
Introduction / Stefan Herbrechter. Section One: Cultural phenomenon. "So tonight I'm gonna party like it's 1999": looking forward to The Matrix / Jon Stratton -- Revolution in The Matrix: a cue call for reflexive sociology / Kimberly Barton -- Enter the Matrix: interactivity and the logic of digital capitalism / Christian Krug and Joachim Frenk. Section Two: Virtualities. Philosophy and The Matrix / Chris Falzon -- Simulacra, simulation and The Matrix / Sven Lutzka -- Is there an exit from virtual reality? Grid and network--from Tron to The Matrix / Elie During. Section Three: Embodiment. Technofantasies and embodiment / Don Ihde -- Queering The Matrix: hacking the digital divide and slashing into the future / Aimee Bahng -- Sexing The Matrix: gender and sexuality in/as cyberfiction / Rainer Emig. Section Four: Theory. Matrix--the new constitution between hardware, software and wetware / Denisa Kera -- The Matrix trilogy and the triumph of virtual reason--territorialized Topoi, nomadic lines / Salah el Moncef bin Khalifa -- The posthuman subject in The Matrix / Stefan Herbrechter -- "New theory?" The posthumanist academy and the beguilements of The Matrix trilogy / Ivan Callus.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Matrix (Motion picture); Matrix (Motion picture); Science fiction films -- Themes, motives; Films de science-fiction -- Thèmes, motifs; PERFORMING ARTS -- Film & Video -- History & Criticism